CATTLE FARMING 4.0 : DEVELOPMENT OF LIVESTOCK SECTOR THROUGH E-AGRIOVEST (DIGITAL BASED INVESTMENT) TO ACCELERATE ECONOMIC GROWTH IN EAST JAVA - Julita Hasanah; Dian Puspasari Ina Ayati; Dimas Brillian Syaban Pramana (East Java Economic Journal, 2019)
East Java had the second highest contribution to National GDP 2017 after Jakarta with a value of 14.61%. Economic growth in East Java was supported by the agricultural sector (13%), while the livestock contributed 20.24% to the East Java agricultural sector. East Java had 20.89% of the national beef cattle population, but beef production was still relatively moderate (23.17%), because East Java farms were dominated by Conventional Farming. East Java beef production didn’t balance national beef consumption which had increased by 4.66%. It was the main cause of fluctuations and volatility in beef prices. The fundamental issue of beef issues in East Java needed to be resolved through the industrial revolution 4.0. The purpose of this study was to determine the characteristics of conventional farming, to arrange the e-agriovest system, and to know the contribution of e-agriovest system to East Java’s GDP. This research was conducted in Jember as a sample area. The study used survey methods and descriptive analytics. Based on the results of research on characteristics of conventional farming, among others (1) the number of small livestock (1-3 tail) (56.67%), (2) the sales period as needed (60%), (3) still using forage feed (100%) , (5) saving livestock function (46.66%) and sales system through blantik (66.67%). Based on East Java livestock data in 2008-2017, the contribution of livestock in East Java had a high potential to be developed in terms of population, production, demand, domestic beef prices, imported beef prices, and GDP. e-agriovest can be simulated to increase beef production by 20%. The existence of e-agriovest had a positive impact on East Java GRDP with a value increase of 2.83%. e-agriovest system is an appropriate implementation strategy in developing the livestock subsector in order to accelerate the acceleration of East Java's economic growth both economically, socially and environmentally. JEL : O4,E2,Q1